A safety and pharmacodynamic study of the highly selective aldosterone synthase inhibitor PB6440 in the cynomolgus monkey. (3rd October 2022) - Pitt, B; Bhatt, D L; Schotzinger, R J; Pacyniak, E; Jowett, J; Lee, J S
Abstract: Background: Aldosterone is an important mediator of hypertension, particularly resistant hypertension, heart failure, and chronic kidney disease. PB6440 is a potent inhibitor of aldosterone synthase (CYP11B2) with high selectivity over the closely related enzyme CYP11B1. In previous studies in cynomolgus monkeys, PB6440 exhibited excellent oral bioavailability and a marked suppression of aldosterone synthesis at doses as low as 1 mg/kg/day. Importantly, no effect was observed on cortisol production nor significant changes noted in plasma concentrations of the steroid precursors 11-deoxycortisol or deoxycorticosterone (DOC), which are dependent on CYP11B1 activity. The purpose of the current study was to assess the safety and pharmacodynamics of higher doses of PB6440 in the cynomolgus monkey in order to determine a therapeutic index prior to initiation of studies in humans. Methods: Male and female cynomolgus monkeys (2/sex/dose group) were administered 0, 10, 30 or 100 mg/kg PB6440 once-daily for 14 days by oral gavage. Assessment of safety was based on mortality, clinical observations, body weights, and clinical and anatomic pathology. Blood samples were also collected for pharmacodynamic analysis, including aldosterone, cortisol, 11-deoxycortisol, DOC, and ACTH. Results: PB6440 was well tolerated at all doses. There were no deaths and no reports of clinical observations at any dose level. Mild decreases in body weight were observed in PB6440-treated animals, which were likely due to the diuretic effects of the compound. PB6440 caused an increase in adrenal weights which was associated with hypertrophy of the adrenal zona fasciculata, a finding which has previously been observed with other aldosterone synthase inhibitors. PB6440 led to marked declines in basal aldosterone levels of −97%, −97% and −98% from baseline at 10, 30 and 100 mg/kg/day, respectively, at 24-hours following the final dose. Despite these clear declines in circulating aldosterone levels, no meaningful changes in cortisol, 11-deoxycortisol, DOC, or ACTH levels were observed, supporting lack of CYP11B1 inhibition. PB6440 led to expected decreases in plasma sodium (up to 7 nmol/L at the high dose). No effect on plasma potassium levels were observed at any dose level. Conclusions: PB6440 was well tolerated in the cynomolgus monkey at doses that are much higher than needed for potent aldosterone suppression based on previous studies. At the highest dose level tested (100 mg/kg), which led to a 98% reduction in basal aldosterone levels, no evidence of significant CYP11B1 inhibition was observed. The absence of an increase in plasma potassium in the presence of a plasma sodium decline merits further study. Thus, PB6440 is a highly selective novel aldosterone synthase inhibitor for the potential treatment of hypertension, heart failure, and chronic kidney disease in humans. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): PhaseBio Pharmaceuticals Inc.